2004
DOI: 10.1002/jgm.701
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional tumor‐selective promoter targeting of E. coli purine nucleoside phosphorylase for pancreatic cancer suicide gene therapy

Abstract: These data confirm and extend the antitumor efficacy of the ePNP/MePdR killing system and demonstrate the feasibility of the transcriptional targeting strategy under tumor marker promoter control and thereby a preferential killing of CEA- and MUC1-producing pancreatic tumor cells. Thus, efficient in vivo gene delivery and transcriptional targeting constitute the major future clinical challenge for a selective pancreatic cancer suicide gene strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Pancreatic cancer-specific cytotoxicity has been achieved in several in vitro and in vivo studies using tumor cell-specific promoters such as carcinoembryonic antigen (CEA), erb-B2, cyclooxygenase-2, Mucin1 (MUC1), and cholecystokinin type A receptor (CCKAR) to drive suicide genes [27][28][29][30][31][32][33]. The insulin gene promoter is a tissue-specific promoter, which is only activated in beta cells of the pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer-specific cytotoxicity has been achieved in several in vitro and in vivo studies using tumor cell-specific promoters such as carcinoembryonic antigen (CEA), erb-B2, cyclooxygenase-2, Mucin1 (MUC1), and cholecystokinin type A receptor (CCKAR) to drive suicide genes [27][28][29][30][31][32][33]. The insulin gene promoter is a tissue-specific promoter, which is only activated in beta cells of the pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…Promoter-driven DNA delivery has been tested in a variety of tumor types using both viral (27,(36)(37)(38) and nonviral vectors (6,10,39). With the former type, coding sequences for metabolic enzymes are typically delivered (e.g., thymidine kinase or cytosine deaminase) to tumor cells, and these expressed enzymes activate prodrugs [ganciclovir (38) and 5-fluorocytosine (40), respectively].…”
Section: Discussionmentioning
confidence: 99%
“…To make SC36 safer for clinical trials, it should be important to develop tumor-specific expression vectors. Deharvengt et al 27 examined the feasibility of a tumor-specific targeting strategy to treat pancreatic cancer by using the human CEA and MUC1 promoters. Cai et al 29 demonstrated the killing effect of PNP/MePdR suicide gene system driven by an AFP promoter AF0.3 on AFP-positive hepatoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] The ePNP/ MePdR system differs from other GDEPT systems, because the toxic metabolites of this system will readily cross the cell membrane and not require direct cell-to-cell contact or the presence of a gap junction. 22 In previous papers, the ePNP/MePdR system has been reported to be an efficient suicide gene/prodrug system with significant antitumor activities on ovarian cancers, 17 gliomas, 23 prostate cancers, 24 melanomas, 25 pancreatic cancers, 26,27 hepatomas 28,29 and bladder tumors. 30 However, an exploitation of this method using attenuated Salmonella as a carrier to deliver the ePNP gene has never been attempted.…”
Section: Introductionmentioning
confidence: 99%